2016
DOI: 10.1007/s00038-016-0787-y
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use among Serbian adults: prevalence and user characteristics

Abstract: Electronic cigarettes are popular in Serbia; one in ten adults had tried them at least once. Because females and young adults were more likely to use e-cigarettes, a targeted response in these specific groups is needed. A standardised methodology for monitoring e-cigarette use should be established and surveys exploring motives for and attitudes towards e-cigarettes use should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This is the one of first studies to explore knowledge, attitudes and use of e-cigarettes in adult population, and to examine differences according to sex, age, place of living, educational status and smoking status. The prevalence rate of current use of e-cigarettes is (5.8%) of all respondents -9.2% men and 4.5% women, which is similar to the rates from studies in Great Britain 3.5% [20], United States 4-7%, France 6%, Australia 7% [21,22] and Serbia 1.6-2.3% [23] but more than relevant data for Croatia from Special Eurobarometer which is only 1% [16].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is the one of first studies to explore knowledge, attitudes and use of e-cigarettes in adult population, and to examine differences according to sex, age, place of living, educational status and smoking status. The prevalence rate of current use of e-cigarettes is (5.8%) of all respondents -9.2% men and 4.5% women, which is similar to the rates from studies in Great Britain 3.5% [20], United States 4-7%, France 6%, Australia 7% [21,22] and Serbia 1.6-2.3% [23] but more than relevant data for Croatia from Special Eurobarometer which is only 1% [16].…”
Section: Discussionsupporting
confidence: 71%
“…The lifetime prevalence is 66.0% -men 53.3% and women 44.6% which is more than in Serbia 8.5 -10.8%, United States 13 -15%, Australia 20%, France 25.7%, Netherlands 40% and in previous research in Croatia 8% [20,[22][23][24]. People from the youngest age group (18-30 years of age) are the ones who tried e-cigarettes the most 60.8%, like in some other studies -48.8% [23]. Almost all (97.9%) participants in our study have heard of e-cigarettes, similar to the American study (91.9%) [25].…”
Section: Discussionmentioning
confidence: 75%
“…Overall, 22 studies were included in the review (Table 1). Of these, 4 of them included data from multiple countries [22][23][24][25], and 18 studies presented data from single countries [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. All included studies were either cross-sectional studies, or cross-sectional baseline findings of longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence was found among those aged 10-24 years (5.5% to 56.6%), followed by those aged 25-39 (13.7% to 25%), 40-65 (5% to 6.7%), and those aged ≥ 65 years (1.3% to 1.6%). For example, in a sample of 5385 Serbians, there were about 3 times more current e-cigarette users among 25-44-year-olds than among 55-64-year-olds (3% vs. 1.1%) [28]. It seems to point to a trend that with increasing age, the use of e-cigarettes decreases.…”
Section: Prevalence Of Using E-cigarettes In the General Populationmentioning
confidence: 99%
“…Our results showed that only 3.6% of the target population used e-cigarettes, which was higher than the average level of e-cigarettes use among all teachers across China (2.4%). Since e-cigarettes came into public view, their use has considerably increased across the world [29]. School personnel, as a special group whose behavior has a profound impact on the students, need to be further monitored for both conventional cigarette smoking behavior and e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%